Comparative adverse event profiles of triplet therapy versus docetaxel-based therapy in patients with metastatic prostate cancer: a multicenter retrospective study - Fumihiko Urabe; Hirokazu Kagawa; Takafumi Yanagisawa; Hidetsugu Takahashi; Masaki Hashimoto; Shuhei Hara; Wataru Fukuokaya; Yu Imai; Kosuke Iwatani; Taro Igarashi; Mahito Atsuta; Kojiro Tashiro; et al. (Prostate International)
Background: To compare adverse event (AE) profiles between patients with prostate cancer receiving triplet therapy (docetaxel, androgen receptor signaling inhibitors [ARSIs], and androgen deprivation therapy [ADT]) and those receiving docetaxel-based therapy (docetaxel and ADT). Additionally, we sought to identify risk factors for severe AEs associated with these treatment regimens. Materials and methods: In this retrospective, multicenter study, we included 359 patients diagnosed with metastatic castration-sensitive prostate cancer (mCSPC) or metastatic castration-resistant prostate cancer (mCRPC) who were treated with docetaxel. We analyzed patient demographics, hematologic and non-hematologic AEs, and risk factors for severe AEs. Logistic regression models were used to assess risk factors. Results: There were no significant differences in the incidence of ≥ grade 3 neutropenia or febrile neutropenia (FN) between the triplet and docetaxel-based therapy groups when stratified by the use of primary prophylaxis. Non-hematologic AEs, especially fatigue, were more frequent in the mCRPC group compared to the triplet therapy group. Primary prophylaxis with granulocyte colony-stimulating factor (G-CSF) significantly reduced the risk of severe neutropenia (odds ratio [OR] 0.092, P < 0.001) and FN (OR 0.13, P = 0.007). Conclusion: This study represents the first real-world analysis comparing the adverse event profiles of triplet therapy and docetaxel-based therapy in Japanese patients with mCSPC, as well as docetaxel-based therapy in those with mCRPC. No significant difference in severe AEs was observed between the therapies. Primary prophylaxis with G-CSF proved critical in reducing severe neutropenia and FN, underscoring its importance in enhancing the safety and efficacy of docetaxel-based therapies.